Perovskite Solar Cells: Is Excess PbI2 Beneficial for Perovskite Solar Cell Performance? (Adv. Energy Mater. 7/2016). Issue 7 (April 2016) - Liu, Fangzhou; Dong, Qi; Wong, Man Kwong; Djurišić, Aleksandra B.; Ng, Annie; Ren, Zhiwei; Shen, Qian; Surya, Charles; Chan, Wai Kin; Wang, Jian; Ng, Alan Man Ching; Liao, Changzhong; et al.
Abstract : In article number 1502206, Aleksandra B. Djurišić and co‐workers discuss whether excess PbI2 is beneficial for perovskite solar cell performance. The presence of unreacted PbI2 is commonly believed to be beneficial to the efficiency of perovskite solar cells. However, it results in an intrinsic instability of the illuminated film even in inert atmosphere, leading to accelerated film degradation under illumination.